Retinoid-mediated transcriptional regulation of keratin genes in human epidermal and squamous cell carcinoma cells. - Stellmach, V (1991)
Vitamin A and other retinoids profoundly inhibit morphological and biochemical features of epidermal differentiation in vivo and in vitro. To elucidate the molecular mechanisms underlying the differential expression of epidermal keratins and their regulation by retinoids, we examined retinoid-mediated changes in total protein expression, protein synthesis, mRNA expression, and transcription in cultured human keratinocytes and in squamous cell carcinoma (SCC-13) cells of epidermal origin. Our studies revealed that the epidermal keratins, K5, K6, K14, and K16, their mRNAs, and their transcripts were diminished relative to actin as a consequence of retinoic acid (RA) treatment. The effects were most pronounced in SCC-13 and were detected as early as 6 hr post-RA treatment, with enhancement over an additional 24-48 hr. Repression was also observed when 5' upstream sequences of K14 or K5 genes were used to drive expression of a chloramphenicol acetyltransferase reporter gene in SCC-13 keratinocytes. Both cell types were found to express mRNAs for the RA receptors alpha and gamma, which may be involved in the RA-mediated transcriptional changes in these cells. The rapid transcriptional changes in epidermal keratin genes were in striking contrast to the previously reported slow transcriptional changes in simple epithelial keratin genes.